An assessment of UMS Pre-University Students' readiness on online examination - Suriana Lasaraiya; Mohd Azrul Abd Rajak; Che Haziqah Che Hussin; Nurliyana Juhan (Global Academic Excellence (M) Sdn Bhd, 2021)
Pandemic COVID-19 has given a significant impact on the education culture whereby online learning has become the main way in teaching and learning activities. In line with the important use of online learning, it is very important to identify whether the students are ready enough for an online class or not. The study on ‘An Assessment of UMS Pre-University Students’ Readiness on Online Examination’ sought to answer the questions about students’ readiness on the preferred mode of learning and the student's readiness on an online examination. The respondents of the study were UMS Pre-University students who enrolled in the Foundation in Science program (AUMS) in the year 2020. Specifically, there was 105 male, and 153 female students were included in the study. Through Google form online survey, the questionnaires were sent through their email and WhatsApp group. Then, the data were gathered, collected, and analysed. Descriptive statistics analysis and item level mean related to students’ internet connectivity is provided in the form of percentage, mean and standard deviations. The study reveals that AUMS students’ internet connectivity was moderately ready for their online examinations, as it depends mainly on their location. If the students are staying in an urban areas, then their internet connections should be good and vice versa. This study also reveals that problems in Wi-Fi connection are the main concern of students’ accessibility to online learning.